Material culture : Präsenz und Sichtbarkeit von Künstlern, Zünften und Bruderschaften in der Vormoderne. - Tacke, Andreas; Münch, Birgit Ulrike; Zentralinstitut für Kunstgeschichte in München; Augustyn, Wolfgang (Petersberg : Michael Imhof Verlag, 2018)
"The 'material turn' has led to stimulating new questions, new research areas and new research perspectives in numerous humanities and social science disciplines. The often quoted 'thinking through things' is essential, especially in the area of the history of collections and museums. Nevertheless, it is astounding that numerous research themes have hardly been worked on despite the immanent connection of objects to the discipline of art history although such research themes form a major area of the pre-modern self-conception of the artist. Speaking of those objects of 'material culture' representing the civic associations in crafts and business to make visible the system of guilds and brotherhoods in a townscape. All those objects making up this area of study play the major role here. The term material culture of the guild and crafts system is to be understood in its broadest possible dimensions, from multi-panel altar to the simple guild cabinet storing the candles for the civic processions. Of interest are the form, effect and function of these objects in their sacred and profane surroundings"--Back cover.
Proceedings of a conference held at Zentralinstitut für Kunstgeschichte in München, February 25-28, 2016.
10 German and 10 English contributions; preface and foreword in German.
boek
Keywords: Arts, Medieval -- Congresses; Arts, Renaissance -- Congresses; Artists -- History -- Congresses; Guilds -- History -- Congresses